Persepsi Mahasiswa Tentang Fenomena Flexing di Media Sosial Perspektif Maqāṣid Syarīʿah - Sultan, Nurul lutfiah; Zulfahmi Alwi; Andi Muhammad Akmal; Abd Rauf Muhammad Amin; Andi Achruh (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This research aims to: (1) understand the reality of the flexing phenomenon on social media; (2) examine its impact on students of UIN Alauddin Makassar; and (3) analyze it from the perspective of Maqāṣid Sharīʿah. Using a field research method with phenomenological and theological approaches, this study explores students' subjective experiences and the relevance of Maqāṣid Sharīʿah, particularly in maintaining religion (hifz al-Din), life (hifz an-Nafs), intellect (hifz al-Aql), lineage (hifz an-Nasl), and wealth (hifz al-Mal). The primary data sources are 10 postgraduate students and 8 undergraduate student representatives from each faculty, selected through purposive sampling, complemented by an interview survey of 39 students. Data were analyzed by reducing negative impacts and mapping behaviors, effects on actors, and effects on others, followed by verification for validity and reliability. The results show that flexing on social media is controversial, causing more harm than benefit, with cases linked to fraud, corruption, and even loss of life. Among UIN Alauddin Makassar students, flexing leads to insecurity, social pressure, and self-comparison, though a few view it as motivational. From the Maqāṣid Sharīʿah perspective, excessive flexing conflicts with values of simplicity, family morals, and prudent wealth management. This research highlights the need for ethical and moral awareness in social media use, urging young people to align online behavior with Islamic teachings through the framework of Maqāṣid Sharīʿah.